1999
DOI: 10.1093/emboj/18.17.4744
|View full text |Cite
|
Sign up to set email alerts
|

Pathological missense mutations of neural cell adhesion molecule L1 affect homophilic and heterophilic binding activities

Abstract: Mutations in the gene for neural cell adhesion molecule L1 (L1CAM) result in a debilitating X-linked congenital disorder of brain development. At the neuronal cell surface L1 may interact with a variety of different molecules including itself and two other CAMs of the immunoglobulin superfamily, axonin-1 and F11. However, whether all of these interactions are relevant to normal or abnormal development has not been determined. Over one-third of patient mutations are single amino acid changes distributed across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
153
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 53 publications
(67 reference statements)
11
153
2
Order By: Relevance
“…7 In cell-cell adhesion assay, Ninj1-transfected macrophages adhered to human umbilical vein endothelial cells 2.2 times more than mock (Mo)-transfected macrophages, which was reversed by Ninj1 antibody treatment (Figure 5c). Many adhesion molecules interact heterophilically as well as homophilically with their family members [28][29][30] and the possibility of heterophilic adhesion of Ninj1 has been also suggested. 19 They showed that peptides containing the adhesion motif of Ninj1 block the basal adhesion of wild-type Jurkat cells, indicating that other molecules with the Ninjurin-like adhesion motif may be involved in heterophilic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…7 In cell-cell adhesion assay, Ninj1-transfected macrophages adhered to human umbilical vein endothelial cells 2.2 times more than mock (Mo)-transfected macrophages, which was reversed by Ninj1 antibody treatment (Figure 5c). Many adhesion molecules interact heterophilically as well as homophilically with their family members [28][29][30] and the possibility of heterophilic adhesion of Ninj1 has been also suggested. 19 They showed that peptides containing the adhesion motif of Ninj1 block the basal adhesion of wild-type Jurkat cells, indicating that other molecules with the Ninjurin-like adhesion motif may be involved in heterophilic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The geometry of homophilic protein interactions at the cell surface varies between parallel "side-toside" interactions such as those observed for B7-1 (45), antiparallel side-to-side interactions as observed in the hemolin structure (46) and proposed for NCAM (47), L1 (48), and PECAM (49,50),…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, binding of neurocan to L1 may inhibit L1 homophilic adhesion by stabilizing the linear conformation of Ig1-4 (18). The potential importance of the horseshoe structure of L1 is underscored by the conservation of residues across species at the domain interfaces between Ig1 to Ig4 and Ig2 to Ig3 and the disproportionate number of these residues in which missense mutations cause developmental abnormalities of the nervous system (21,22,29).…”
Section: Discussionmentioning
confidence: 99%
“…The Leu-120-Val mutation results in the loss of Sema3A regulation of L1-neuropilin interactions but does not affect L1 homophilic binding (30). On the other hand, the Gly-121-Ser mutation reduces L1 homophilic binding by 90% and decreases L1 interactions with F11 and contactin (21). Thus, the binding of ethanol in the region of these disease-causing mutations could disrupt development by inhibiting homophilic or heterophilic interactions of L1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation